Proceedings of MOL2NET 2016, International Conference on Multidisciplinary Sciences, 2nd Edition 2017
DOI: 10.3390/mol2net-02-03897
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the uncertainty of the operational parameters in obtaining cane syrup in sensorial attributes

Abstract: Problems of variability in the design of equipment, the availability of equipment, the changes in the environment and in future changes which have been extensively investigated in order to determine the chances of success in environmental, technological and economic matters. This research considers the variability of the operational parameters in the quality of the final product, as an element in the process design, this approach is not an usual activity. Some previous studies on the production of sugarcane sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 2 publications
1
4
0
Order By: Relevance
“…It is appreciated that being an artisan process, there is no pH control since the liming method is empirical, coinciding with that reported by Guerra and Mujica [22]. However, this variability of the operating parameter affects, according to Cerda [23], the quality of the final product. The level behavior is presented in figure 9.…”
Section: Writing and Transmission Of Variables Onlinesupporting
confidence: 56%
See 2 more Smart Citations
“…It is appreciated that being an artisan process, there is no pH control since the liming method is empirical, coinciding with that reported by Guerra and Mujica [22]. However, this variability of the operating parameter affects, according to Cerda [23], the quality of the final product. The level behavior is presented in figure 9.…”
Section: Writing and Transmission Of Variables Onlinesupporting
confidence: 56%
“…In the case of pH, a difference of 2.99 is appreciated. The variability of this operating parameter impacts the quality of cane honey, as reported by Cerda [23]. These differences may be because most sugar mills do not control acidity; it is carried out empirically, according to Mosquera, Carrera, and Villada [24].…”
Section: Operational Parameters As Design Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, complementing the experimental results with new theoretical calculations (simulations), as well as with an uncertainty analysis, can reduce the number of defects. However, this evaluation is focused on a subsystem of quality analysis that can contribute to decision making during process design, which should consider technical, environmental, economic, and quality requirements (Cerda Mejía et al, 2017;Pérez-Martínez et al, 2012).…”
Section: Determination Of Uncertainty By the Gum Methodologymentioning
confidence: 99%
“…It was found that income reduces in the amount of 696 429 USD in a year of production (Table 6). This means that the data provided by Cerda Mejía et al (2017) andQuezada Moreno et al (2016) would have a huge economic impact. The negative effect of the number of defective products on the income for this iteration ranges between 30% and 52% in the range of the studied productions.…”
Section: Economic Benefitmentioning
confidence: 99%